Analysis of potential establishment of sharia public financing bank (BPRS) In Lebak Regency - Dinar Rahmayanti; Nur S Buchari (Jurnal Ekonomi dan Perbankan Syariah, 2021)
This study aims to determine the feasibility of establishing a Sharia Rural Bank (BPRS) in Lebak Regency. The majority of the population in Lebak Regency is Muslim, but there is no BPRS. This study also aims to determine the most effective strategy for the establishment of a BPRS in Lebak Regency. The method chosen in this research is descriptive qualitative using the SWOT analysis tool. To determine the strategy, the results of the SWOT analysis are processed by the QSPM method. The results of the research on the IE matrix show that the  establishment of the BPRS in Lebak Regency is in cell I, which is growing and building. The strategic priority is to improve the image in society by emphasizing the principles of Islamic economics with a total value of 7, establishing the first BPRS in Lebak Regency with a value of 7, embracing local governments to participate in supporting the existence of Islamic banks with a total value of 7, and conducting education and outreach to the public. about Islamic banking with a total value of 7. This study concludes that Lebak Regency is worthy of establishing a Sharia Peoples Financing Bank.